An integrated tool for virtual restoration of Byzantine icons - Maronidis, Anastasios; Voutounos, Chrysanthos; Lanitis, Andreas (My University, 2013)
An integrated tool that can be used for damage detection, shape restoration and texture restoration of faces appearing in Byzantine icons, is presented. The damage detection process involves the estimation of residuals obtained after the coding and reconstruction of face image regions using trained Principal Component Analysis (PCA) texture models. Shape restoration is accomplished using a model-based approach that employs a 3D shape model generated by taking into account a set of geometrical rules adopted by Byzantine style iconographers. Texture restoration is performed using a customized version of the recursive PCA technique. For this purpose dedicated PCA texture models representing different categories of faces appearing in icons, are used. All methods developed as part of the project are incorporated into a user-friendly application, which can be utilized by both amateurs and professionals. Indicative visual and quantitative results show the potential of the developed application.
Keywords: Cultural heritage preservation; Icon restoration; Occlusion detection; Shape restoration; Texture restotration